Acrylic bone cement in total joint arthroplasty: A review. Issue 5 (29th February 2016) - Saleh, Khaled J.; El Othmani, Mouhanad M.; Tzeng, Tony H.; Mihalko, William M.; Chambers, Monique C.; Grupp, Thomas M.
ABSTRACT: Acrylic bone cement has a variety of applications in orthopedic surgery. Primary uses in total arthroplasties are limited to prostheses fixation and antibiotic delivery. With the large number of total joint arthroplasties expected to continue to rise, understanding the role bone cement plays in the success of total joint arthroplasty can have a significant impact on daily practice. The literature is inconclusive on whether cemented or cementless fixation technique is superior, and choice of fixation type is mainly determined by surgeon preference and experience. Surgeons should understand that if poor techniques exist, short‐term outcomes of the replaced joint may be at risk. Statement of clinical significance : This article attempts to clarify some points of bone cement use through a review of the mechanical properties related to bone cement, a comparison to alternative materials, influence of additives, and the effects on surgical outcomes. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:737–744, 2016.